2D finite element simulation of mixed mode fatigue crack propagation for CTS specimen - Abdulnaser M. Alshoaibi (Journal of Materials Research and Technology, 2020)
Damage tolerance theory and the design of safe life are used for mechanical components of importance and in such instances determination of fatigue life using computational strategies are essentials. This paper proposes a formulation of the finite element method to analyze fatigue crack propagation issues according to the linear elastic fracture mechanics (LEFM) theory. The simulation of crack growth was numerically simulated using formulated source code written by Visual FORTRAN language. The advancing front method theory is used to generate the mesh. The trajectory of crack growth was determined using the maximum circumferential stress criterion and the related stress intensity factors were calculated using the equivalent domain integral method. The calculation of mixed mode fatigue life under constant amplitude condition is executed using the Paris law model for two different loading angles. The calculated values of ΔKeq were compared with the experimental and analytical data for various proposed models for various loading angles. The obtained results of the present study consistently achieve results observed to be near to the experimental data in the literature for fatigue life prediction and crack path estimation.